Handbook of supportive and palliative radiation oncology - Krishnan, Monica S. (Academic Press, 2017)
Handbook of Supportive and Palliative Radiation Oncology serves as a practical tool and rapid reference to assist radiation oncology practitioners in direct patient care with common palliative care issues. Containing the most recent advances in translational palliative care research, each chapter is organized in a succinct fashion to discuss major symptom burdens, suggested assessment, and various management options. Each symptom and disease section is written to be a rapid, practical guide for clinicians on the floor. The book starts with general approaches in palliative radiation oncology that are followed by a section that focuses on common symptoms in palliative care and their management. The next section of the book is devoted to site and disease-specific evaluation, intervention, and management. This handbook provides general guidelines and management recommendations for common clinical vignettes encountered by palliative radiation oncology practitioners and supported by palliative radiation oncology research. Concise references are cited to support treatment recommendation. Provides a quick reference for the busy clinician Details standard of care resources for researchers of palliative and supportive care Contains updated standards of care for palliative medicine and a list of common medications and dosages Includes a comprehensive index by symptom and condition to facilitate quick reference.